2020
DOI: 10.1016/j.tranon.2020.100802
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Tumor and Stromal Sources of MicroRNAs Linked to Metastasis in Cutaneous Melanoma

Abstract: MicroRNA (miRNA) dysregulation in cancer causes changes in gene expression programs regulating tumor progression and metastasis. Candidate metastasis suppressor miRNA are often identified by differential expression in primary tumors compared to metastases. Here, we performed comprehensive analysis of miRNA expression in The Cancer Genome Atlas (TCGA) skin cutaneous melanoma (SKCM) tumors (97 primary, 350 metastatic), and identified candidate metastasis-suppressor miRNAs. Differential expression analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
(123 reference statements)
1
3
0
Order By: Relevance
“…Initial experimentation in our study revealed that miR-141-3p was poorly expressed, and FGF13 was highly expressed in CM tissues. In line with our data, Watt et al [37] also previously documented downregulation of miR-141 in melanoma. Subsequent microarray-based screening analyses in our study highlighted that there was a correlation among the FGF13, CDH1, SYK, and FN1 genes in the context of melanoma.…”
Section: Discussionsupporting
confidence: 93%
“…Initial experimentation in our study revealed that miR-141-3p was poorly expressed, and FGF13 was highly expressed in CM tissues. In line with our data, Watt et al [37] also previously documented downregulation of miR-141 in melanoma. Subsequent microarray-based screening analyses in our study highlighted that there was a correlation among the FGF13, CDH1, SYK, and FN1 genes in the context of melanoma.…”
Section: Discussionsupporting
confidence: 93%
“…Although the overlap of miRNAs from different HNSCC studies is generally relatively small, 12 of the differentially expressed miRNAs between HPV-positive and HPV-negative tumours ( Table S1 ) and five signature miRNAs (hsa-miR-155-5p, hsa-miR-181a-5p, hsa-miR-18a-5p, hsa-miR-378a-3p, hsa-miR-455-3p) were previously reported to be HPV-associated [ 1 , 5 , 6 , 7 , 8 , 9 , 10 , 12 ]. The analysis of bulk samples does not allow differentiation between tumour and stromal miRNA sources (e.g., infiltrated lymphocytes), and could be a cause for the rather small differences in detected miRNA levels [ 36 ]. Nevertheless, the miRNA analyses enabled the identification of a 24-miRNA signature that, in addition to miRNA expression differences in tumour cells, could also be determined by those of the tumour microenvironment of HPV-positive and HPV-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, we restricted our further analyses to studies that clearly identified the disease subtypes in each cohort and attributed at least one dermatopathologist was attributed as reviewing each specimen. We identified twenty-one studies that met these criteria [ 47 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ].…”
Section: Micrornas Consistently Associated With Melanoma Progressionmentioning
confidence: 99%
“…However, in addition to directionality, the magnitude of differential expression should also be considered when assessing the biological function of a miRNA ( Figure 2 , Figure 3 and Figure 4 ). MiR-211 is usually detectable in primary melanoma specimens, and its expression is approximately 2–10-fold greater in melanocytic nevi [ 47 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. In comparison, expression of the miRNA is routinely reported at 10 2 –10 4 -fold greater in cultured NHEMs, as compared to cultured human melanoma lines [ 112 , 118 , 127 , 129 ].…”
Section: Mir-211-5p Expression Confers Robustness To Pigmented Cellsmentioning
confidence: 99%